2005
DOI: 10.1051/0004-6361:20042590
|View full text |Cite
|
Sign up to set email alerts
|

Production of the large scale superluminal ejections of the microquasar GRS 1915+105 by violent magnetic reconnection

Abstract: We propose here that the large-scale superluminal ejections observed in the galactic microquasar GRS 1915+105 during radio flare events are produced by violent magnetic reconnection episodes in the corona just above the inner edge of the magnetized accretion disk that surrounds the central ∼10 M black hole. The process occurs when a large-scale magnetic field is established by a turbulent dynamo in the inner disk region with a ratio between the gas+radiation and the magnetic pressures β 1, implying a magnetic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

19
231
2
12

Year Published

2006
2006
2014
2014

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 219 publications
(264 citation statements)
references
References 37 publications
19
231
2
12
Order By: Relevance
“…Large scale magnetic reconnection events may be at the origin of large scale transient jets in microquasar systems (de Gouveia dal Pino & Lazarian 2005;de Gouveia Dal Pino et al 2010;Kowal et al 2011;Dexter et al 2014), for example via a magnetic field reversal accreted onto a magnetically arrested disk. Reconnection then occurs in the accretion disk coronae, near the black hole, where particle densities and magnetic fields are high.…”
Section: Objects and Orders Of Magnitudementioning
confidence: 99%
See 1 more Smart Citation
“…Large scale magnetic reconnection events may be at the origin of large scale transient jets in microquasar systems (de Gouveia dal Pino & Lazarian 2005;de Gouveia Dal Pino et al 2010;Kowal et al 2011;Dexter et al 2014), for example via a magnetic field reversal accreted onto a magnetically arrested disk. Reconnection then occurs in the accretion disk coronae, near the black hole, where particle densities and magnetic fields are high.…”
Section: Objects and Orders Of Magnitudementioning
confidence: 99%
“…It is a candidate for explaining (i) particle acceleration at pulsar wind termination shocks (Kirk & Skjaeraasen 2003;Pétri & Lyubarsky 2007;Sironi & Spitkovsky 2011a); (ii) the flat radio spectra from galactic nuclei and AGNs (Birk et al 2001) and from extragalactic jets (Romanova & Lovelace 1992); (iii) GeV flares from the Crab nebula (Bednarek & Idec 2011;Uzdensky et al 2011;Cerutti et al 2012aCerutti et al ,b, 2013; (iv) flares in active galactic nuclei (AGN) jets (Giannios et al 2009) or in gamma-ray bursts (Lyutikov 2006a;Lazar et al 2009); (v) the heating of AGN and microquasar coronae and the observed flares (Di Matteo 1998;Merloni & Fabian 2001;Goodman & Uzdensky 2008;Reis & Miller 2013;Romero et al 2014;Zdziarski et al 2014); (vi) the heating of the lobes of giant radio galaxies (Kronberg et al 2004); (vii) transient outflow production in microquasars and quasars (de Gouveia dal Pino & Lazarian 2005;de Gouveia Dal Pino et al 2010;Kowal et al 2011;Dexter et al 2014); (viii) gamma-ray burst outflows and non-thermal emissions (Drenkhahn & Spruit 2002;Giannios & Spruit 2007;McKinney & Uzdensky 2012); (ix) X-ray flashes (Drenkhahn & Spruit 2002); or (x) soft gamma-ray repeaters (Lyutikov 2006b;Uzdensky 2011).…”
Section: Introductionmentioning
confidence: 99%
“…1. A detailed description of the scenario adopted is given in de Gouveia Dal Pino & Lazarian (2005). Here we briefly present the assumptions made.…”
Section: A Simple Reconnection Scenario In the Inner Accretion Disk/cmentioning
confidence: 99%
“…Besides, because the reconnection mechanism is operating at the interface region between the inner disk and the central source, the choice of a geometrically thin accretion disk (rather than a thick one) is not a crucial point for our model. of the magnetic flux in this region (e.g., Merloni 2003;Livio et al 2003;Tagger et al 2004;de Gouveia Dal Pino & Lazarian 2005;McKinney & Blandford 2009). Even without any dynamo action, a net poloidal field could be built in the inner diskcorona region simply due to advection of existing magnetic flux from the large radii.…”
Section: A Simple Reconnection Scenario In the Inner Accretion Disk/cmentioning
confidence: 99%
See 1 more Smart Citation